Complete Genome Sequence of Clostridium estertheticum DSM 8809, a Microbe Identified in Spoiled Vacuum Packed Beef - Yu, Zhongyi; Gunn, Lynda; Brennan, Evan; Reid, Rachael; Wall, Patrick G.; Gaora, Peadar Ó.; Hurley, Daniel; Bolton, Declan; Fanning, Séamus (Frontiers in Microbiology, 2016)
Blown pack spoilage (BPS) is a major issue for the beef industry. Aetiological agents of BPS involve members of a group of Clostridium species, including Clostridium estertheticum which has the ability to produce gas, mostly carbon dioxide, under anaerobic psychotrophic growth conditions. This spore-forming bacterium grows slowly under laboratory conditions, and it can take up to 3 months to produce a workable culture. These characteristics have limited the study of this commercially challenging bacterium. Consequently information on this bacterium is limited and no effective controls are currently available to confidently detect and manage this production risk. In this study the complete genome of Clostridium estertheticum DSM 8809 was determined by SMRT® sequencing. The genome consists of a circular chromosome of 4.7 Mbp along with a single plasmid carrying a potential tellurite resistance gene tehB and a Tn3-like resolvase-encoding gene tnpR. The genome sequence was searched for central metabolic pathways that would support its biochemical profile and several enzymes contributing to this phenotype were identified. Several putative antibiotic/biocide/metal resistance-encoding genes and virulence factors were also identified in the genome, a feature that requires further research. The availability of the genome sequence will provide a basic blueprint from which to develop valuable biomarkers that could support and improve the detection and control of this bacterium along the beef production chain.